Intestinal Microbiota and Gene Expression Reveal Similarity and Dissimilarity Between Immune-Mediated Colitis and Ulcerative Colitis - Sakai, Kazuko; Sakurai, Toshiharu; De Velasco, Marco A.; Nagai, Tomoyuki; Chikugo, Takaaki; Ueshima, Kazuomi; Kura, Yurie; Takahama, Takayuki; Hayashi, Hidetoshi; Nakagawa, Kazuhiko; Kudo, Masatoshi; Nishio, Kazuto (Frontiers in Oncology, 2021)
Immune checkpoint inhibitors (ICIs) have become the standard of care for several cancers. However, ICI therapy has also been associated with various immune-related adverse events (irAEs). Clinical manifestations of immune-related colitis resemble those of inflammatory bowel diseases such as ulcerative colitis (UC). The composition of the bowel microflora is thought to influence the development of inflammatory bowel disease and irAE colitis. We profiled the gene expressions and microbe compositions of colonic mucosa from patients with solid cancers receiving anti-PD-L1 antibody treatment; we then compared the expression profiles associated with irAE colitis with those associated with UC. The pathway enrichment analysis revealed functional similarities between inflamed regions of irAE colitis and UC. The common enriched pathways included leukocyte extravasation and immune responses, whereas non-inflamed mucosa from patients with irAE colitis was distinct from patients with UC and was characterized by the recruitment of immune cells. A similarity between the microbiota profiles was also identified. A decreased abundance of Bacteroides species was observed in inflamed regions from both irAE colitis and UC based on a microbiota composition analysis of 16S rDNA sequencing. Pathways associated with molecule transport systems, including fatty acids, were enriched in inflamed and non-inflamed irAE colitis and inflamed UC, similar to Piphillin-inferred KEGG pathways. While UC is characterized by local regions of inflammation, ICI treatment extends to non-inflammatory regions of the colonial mucosa where immune cells are reconstituted. This analysis of the similarity and heterogeneity of irAE colitis and UC provides important information for the management of irAE colitis.